Development of Climate Smart Agriculture and Climate Information System Relevant Curricula for Staff, Students and other stakeholders in Universities in Africa - Rukarwa, Jolyn R; Egeru, Anthony; Mwanjololo, Jackson GM; Nakayiwa, Florence (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impacts of CGIAR Climate Research for Africa project (AICCRA), working through CCAFS, intends to make CGIAR-led cutting-edge science practices/technologies/tools available throughout Africa; especially in Sub-regions extremely vulnerable to climate change. The Regional Universities Forum for Capacity Building in Agriculture (RUFORUM), a network of 150 universities in 38 countries spanning the whole African continent is a partner in the AICCRA project. RUFORUM’s contribution in the AICCRA project is focused on mobilising African universities, create awareness and enhance the use of Climate Smart Agriculture (CSA) and Climate information services (CIS) knowledge and products developed by the CGIAR Centres and other research institutions engaged in CSA and CIS. Enhancing the use of CSA and CIS involves capacity, knowledge and technology audits at national and institutional level, mobilise CGIAR and other research centres to provide CSA and CIS knowledge, technology and skills and training of faculty to deploy the CSA and CIS products in training, research and outreach. Knowledge transfer and capacity-building activities therefore form the central part of RUFORUM’s participation in the AICCRA project.